The role of social policies in the education of children and poor mothers in Salvador, Bahia - Gomes, Cristina (Advances in Social Sciences Research Journal, 2017)
This article explores the narratives of women beneficiaries of different social policies in the Metropolitan Region of Salvador, Bahia, Brazil, analyzing mothers discourses, attitudes and practices in the relationship to their children and, in particular, their commitment to supporting school tasks and their participation in school activities. Additionally, and especially, it looks at their daily work to instill the value of education, as well as practices and commitments between generations of mothers and children with the aim of preparing children with the aim of preparing the new generations to reach a higher level of human development, greater autonomy and increased well-being in their future trajectories. The qualitative methodology was applied: sixteen interviews with beneficiary mothers of social policies in the Metropolitan Region of Salvador, and results were explored with the method of Speech Analysis. Results show that mothers from poor families who receive the benefits of social policies are inter-generationally involved with their commitments. Mothers were even returning to schools, both for personal fulfillment and to give their children an example of the high value that they give to education.